Bridging science and action: Leveraging decision-support tools for transitions to regenerative agriculture - Dao Thu, Hang Thi; Mponela, Powell; Philp, Joshua; Van Der Hoek, Rein; Vongkhamho, Simone; Jalonen, Riina; Lopez, Santiago; Atieno, Mary (2025)
A workshop titled "Bridging Science and Action: Leveraging Decision-Support Tools for Transitions to Regenerative Agriculture" was convened on November 24, 2025 in Vientiane, The Lao People’s Democratic Republic (Laos). The event brought together participants from government agencies, research institutions, universities, and development partners across Laos and Cambodia, alongside technical experts from the Alliance of Bioversity International and CIAT and CIMMYT. The primary objective was to bridge the gap between scientific innovation and practical field application by introducing a suite of Decision-Support Tools (DSTs) for regenerative agriculture, exploring their use through real case studies, and identifying pathways for institutional integration. A key focus was initiating discussions on establishing a regional Community of Practice to ensure the sustained development and adoption of these tools.